Tears and Cheers in Jombang: Some Notes on the 33rd Nahdlatul Ulama Congress - Dadi Darmadi (Studia Islamika, 2016)
In the midst of the scorching heat and dry weather in Jombang, in the month of August 2015, the Nahdlatul Ulama (NU) finally chose K.H. Dr. Said Aqil Siradj as the Chairman of NU. The NU’s 33rd Congress (Muktamar), held in Jombang, East Java, re-elected him for his second term in office in this historical Congress, which was loaded with heat, competition, and compromise.This time the Congress theme was “Upholding Islam Nusantara for Indonesia and World Civilization.” Islam Nusantara, literally meaning “Islam of the archipelago,” may connote different things for different people. It may mean Islam that is rooted in local values, or the kind of Islam that has been promoted by scholars, traders and missionaries with peace, not war. Or, it could suggest a form of Islam that resulted from these various elements. But speaking to an audience weeks before the Congress, Said Aqil Siradj concluded that, as the largest Muslim mass organization in Indonesia, NU felt obliged to remind everyone about the importance of integrating the prinsip kebangsaan (national principles) in conducting worship (beribadah) and implementing religious beliefs (kepercayaan beragama). The theme was strengthened not only in the lively public discussions, book launches and book exhibitions across Jombang, but also in the way NU scholars framed their debates and arguments in the Bahsul Masail forums. The latter is a primary and prestigious forum among NU scholars to discuss important socio-religious issues and produce NU’s formal and strategic decisions.DOI: 10.15408/sdi.v23i1.3317